KECEPATAN MEMBACA EFEKTIF TEKS EKSPLANASI SISWA KELAS XII IPS SMA NEGERI 8 PEKANBARU - Agatha Sella Angraeni; Abdul Razak; Nursal hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the effective reading skills of explanatory texts of students of class XII IPS High School 8 Pekanbaru and describe the average effective reading speed of explanatory texts per group of students in class XII IPS Senior High School 8 Pekanbaru. In an effort to achieve the objectives of this study quantitative methods were used and data collection techniques in the form of a set of objective test tools containing 16 items and 4 alternative answers. Then the results of inj research, namely the speed of effective reading of explanatory texts of students of class XII IPS in SMA Negeri 8 Pekanbaru are very low category and there is a difference in the average effective reading speed of explanatory texts per group.Key Words: Effective reading speed, explanation text.